Training workload controls applicable in elite women's volleyball - Maksimenko, I. G.; Maksimenko, G. N.; Zhilina, L. V.; Bayeva, D. N. (Theory and Practice of Physical Culture, 2019)
Training system excellence issues are ranked among the top priorities by every modern sport discipline including volleyball. Objective of the study was to experimentally prove benefits of an informative and dependable tests and training workload control methods for application in elite women`s volleyball. Sampled for the study were with 19 elite players whose performance was tested and analyzed by the following methods: theoretical analysis; training process monitoring; functionality tests including the HR tests, energy cost tests by Polar Team System; quasi-stationary cortical activity tests; biomedical tests; and statistical data processing toolkit. The test and performance control method was found highly informative, dependable and efficient and therefore may be recommended for the training system quality improvements in the training micro- and meso-cycles. Particularly beneficial in the test array were found the HR variation and energy cost tests to rate effects of the training workloads on elite women players.